2012
DOI: 10.1093/cid/cis899
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Severity, and Prediction of Tuberculous Meningitis Immune Reconstitution Inflammatory Syndrome

Abstract: Tuberculous meningitis (TBM) immune reconstitution inflammatory syndrome is a severe complication of antiretroviral therapy in human immunodeficiency virus–associated TBM. We found that high cerebrospinal fluid neutrophil counts and Mycobacterium tuberculosis culture positivity at TBM presentation characterize, and cytokine concentrations predict, this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
158
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 37 publications
3
158
0
3
Order By: Relevance
“…This temporary exacerbation of TB symptoms and signs is mainly ascribed to the effects of improved immune function, although a "hypersensitivity" reaction to antigens released by killed TB bacilli may also contribute. Although temporary, central nervous system IRIS (resulting from TBM) is associated with rapid clinical deterioration and poor outcomes (Marais et al 2013c). Care should also be taken to differentiate IRIS from superimposed infections, poor adherence, and drug-resistant disease (Marais et al 2013c).…”
Section: Tuberculosis In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This temporary exacerbation of TB symptoms and signs is mainly ascribed to the effects of improved immune function, although a "hypersensitivity" reaction to antigens released by killed TB bacilli may also contribute. Although temporary, central nervous system IRIS (resulting from TBM) is associated with rapid clinical deterioration and poor outcomes (Marais et al 2013c). Care should also be taken to differentiate IRIS from superimposed infections, poor adherence, and drug-resistant disease (Marais et al 2013c).…”
Section: Tuberculosis In Childrenmentioning
confidence: 99%
“…Although temporary, central nervous system IRIS (resulting from TBM) is associated with rapid clinical deterioration and poor outcomes (Marais et al 2013c). Care should also be taken to differentiate IRIS from superimposed infections, poor adherence, and drug-resistant disease (Marais et al 2013c). …”
Section: Tuberculosis In Childrenmentioning
confidence: 99%
“…Prior studies have found multiple immunological abnormalities in association with TB-IRIS, including hyperactivation of M. tuberculosis Ag-specific T cells (6,10), leading to expansion of highly activated (11) polyfunctional CD4 + T cells (12), excessive production of proinflammatory cytokines (13)(14)(15)(16), dysfunction of NK cells (17,18), an increased frequency of neutrophils (19), or perturbation in NKT cells (20,21). The immunopathological mechanisms underlying the development of TB-IRIS are not fully understood, and the complex interplay between different arms of the immune system in TB-IRIS remains to be determined.…”
mentioning
confidence: 99%
“…In an observational study from Cape Town, 47% of TBM patients developed TBM-IRIS at a median of 14 days after ART initiation, while mortality due to TBM-IRIS was 12.5% (2/16). [14] Factors at TBM presentation associated with subsequent TBM-IRIS included high CSF neutrophil count and high CSF bacillary load (reflected by M. tuberculosis culture positivity). Corticosteroids are the only evidence-based treatment currently available for TB-IRIS.…”
Section: Paradoxical Tbm-irismentioning
confidence: 99%